Average miniature post-synaptic potential size is inversely proportional to membrane capacitance across neocortical pyramidal neurons of different sizes - Dervinis, Martynas; Major, Guy (Frontiers in Cellular Neuroscience, 2025)
In chemical synapses of the central nervous system (CNS), information is transmitted via the presynaptic release of a vesicle (or ‘quantum’) of neurotransmitter, which elicits a postsynaptic electrical response with an amplitude termed the ‘quantal size.’ Measuring amplitudes of miniature postsynaptic currents (mPSCs) or potentials (mPSPs) at the cell soma is generally thought to offer a technically straightforward way to estimate quantal sizes, as each of these miniature responses (or minis) is generally thought to be elicited by the spontaneous release of a single neurotransmitter vesicle. However, in large highly-branched neurons, a somatically recorded mini is typically massively attenuated compared with at its input site, and a significant fraction are indistinguishable from (or canceled out by) background noise fluctuations. Here, using a new software package called ‘minis,’ we describe a novel quantal analysis method that estimates the effective ‘electrical sizes’ of synapses by comparing events detected in somatic recordings from the same neuron of (a) real minis and (b) background noise (with minis blocked pharmacologically) with simulated minis added by a genetic algorithm. The estimated minis’ distributions reveal a striking inverse dependence of mean excitatory mPSP amplitude on total cell membrane capacitance (proportional to cell size, or more exactly, extracellular membrane surface area) suggesting that, in rat somatosensory cortex at least, the average charge injected by single excitatory synapses (ca. 30 fC) is conserved across neocortical pyramidal neurons of very different sizes (across a more than three-fold range).